Análise da compatibilidade de mistura de solo argiloso com cinzas volantes de carvão mineral sujeita a percolação por diferentes fluidos - Bastos, Ícaro José Fernandes Santos (2023)
In environmental works, such as solid waste landfills and tailings dams, waterproofing systems are commonly required, with a view to functioning as waterproofing barriers (liners) to contain pollutants. The materials used as waterproofing barriers must have low hydraulic conductivity, watertightness, weathering and shear resistance, durability, in addition to adequate compatibility with different percolating fluids. Given this context, this research aims to evaluate the influence of the contact of different percolating fluids on clayey soils and mixtures of these with residues from the burning of mineral coal (ash), on the hydromechanical behavior of such materials. For this, mineral coal ashes from a thermoelectric plant in the State of Ceará, kaolinitic clay obtained from a deposit in the Metropolitan Region of Fortaleza (RMF) and bentonite clay provided by a company in the capital of Ceará were used as materials. Three (3) percolating fluids were also used, which are distilled water, saline solution and manure, collected at the Metropolitan Sanitary Landfill West of Caucaia (ASMOC). Two mixtures were proposed in this research, with 20% ash + 80% kaolinite clay (20C80CAU) and 80% ash + 20% bentonite (80C20B). The experimental program consisted of physical-chemical and mineralogical characterization tests, such as Xray diffraction tests, infrared absorption spectroscopy (FTIR), thermogravimetric analysis, sorbent complex and the determination of the hydrogen potential (pH) and the electrical conductivity (EC); geotechnical characterization tests, such as real density, granulometry and consistency limits; Proctor Normal compaction test; in addition to geotechnical tests for characterizing the hydromechanical behavior of mixtures and soils subjected to the flow of three percolating fluids, such as permeability tests, oedometric consolidation tests and simple compressive strength tests. As a result, it was observed that all soils and mixtures analyzed are made up of fine material, with kaolinite and bentonite classified as high compressibility clays and ash as low compressibility silts. Thermoelectric waste and mixtures 20C80CAU and 80C20B were classified as Class II-A (non-hazardous and non-inert), which enables their use, from an environmental point of view, for different geotechnical purposes. The ashes did not show the desired hydraulic conductivity for their applications alone as a waterproofing material. However, bentonite, kaolinite soil and idealized mixtures have adequate permeabilities for use in impermeable barriers, with permeability coefficients lower than 10–7 cm/s. With regard to compatibility with percolating fluids, it was concluded that the interaction of the saline solution promoted improvement in the geotechnical characteristics for both investigated mixtures, reducing compressibilities and increasing the resistance to simple compression by up to 10.4%. However, the slurry weakens the waterproofing layer for both mixtures, promoting an increase in hydraulic conductivity and compressibility and a reduction of up to 14.7% in the resistance to simple compression. Thus, it was concluded that it is necessary that the projects of waterproofing layers use tests in which leachate is used as a percolator as a basis, given the high capacity to change the hydromechanical properties of the materials.